PENGARUH LOKASI DAN STRATEGI PEMASARAN TERHADAP PENJUALAN BAKSO BAKAR JUMBO ANTUM ARSYA DI JL.TEMPULING MEDAN, SUMATERA UTARA - Asshifa Nazila Aridzki; Fitriyani Dalimunthe; Muhammad Zikri Alshaufi; Zainarti Zainarti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the effect of location and marketing strategy on the sales of Bakso Bakar Jumbo Antum Arsya. With a quantitative and qualitative approach, this research identifies key factors that influence sales success. Data was collected through customer surveys, interviews with management, and social media analysis. The results show that a strategic location and the implementation of effective marketing strategies significantly increase sales. The findings provide insights for culinary entrepreneurs in growing their business. Translated with DeepL.com (free version).